Analisis Klaim Asuransi Pada Produk Brilliance Hasanah Sejahtera dalam Meminimalisir Resiko Jiwa Dan Investasi (Studi Kasus PT. Sun Life Financial Syariah Cabang Medan) - Anisa Rahmadhani; Tuti Anggraini; Muhammad Lathief Ilhamy Nasution (LPPM Universitas Labuhanbatu, 2023)
This study aims to determine insurance claim procedures and decision making process for insurance claims for Brilliance Hasanah Sejahtera products in minimizing life and investment risks in PT Sun Life Financial Syariah Medan Branch. This type of research uses qualitative research methods. Data collection techniques in this study were carried out by observation, interviews, literature and documentation at PT Sun Life Financial Syariah Medan Branch. The results of this study indicate that the procedure for submitting Brilliance Hasanah Sejahtera insurance claims is not difficult. If a participant submits a claim, first understand the conditions required by Sun Life. And if the participant submits a claim by filling out the form honestly and the completeness of the files is in accordance with PT Sun life's requirements, the claim will be approved and the claims department has a standard claim process of 14 working days for complete every incoming claim with a record that all requirements and documents have been fulfilled. Claims can be postponed if there is a shortage of documents, the company will ask 8participants to complete the data, as a result, claims will be postponed before everything is done complete. But claims can be rejected if irregularities are found, no right, and other causes that are not allowed in insurance.